Unravelling Students’ Attitudes Toward Lifelong Exercise - Evangelou, Efstathia; Digelidis, Nikolaos; Krommidas, Charalampos (Physical Education Theory and Methodology, 2024)
Background. A central purpose of learning in physical education (PE) is to facilitate students’ physical development and competence that determine lifelong engagement in exercise. Therefore, exploring and understanding students’ attitudes toward lifelong exercise contributes significantly to achieving it. Objectives. Two studies examined students’ attitudes toward lifelong exercise. The first study focused on using social and personal variables as predictors. The second study involved a repeated measures design to determine if there were differences in attitudes as students progressed to the next grade and between schools. Additionally, the study aimed to investigate whether there were variations in attitudes based on the students’ physical activity levels. Materials and methods. In the first study, 752 students of the 7th and 10th grades participated, representing 47 classes from 14 schools. Then, after conducting a repeated measures analysis one academic year later, from the initial sample, 460 students formed two cohorts, comprising Grades 7–8 and 10–11. All factors were internally consistent and well-defined by the variables. The first study used hierarchical linear regression to ascertain whether social and personal variables could be identified as predictors of students’ attitudes toward lifelong exercise. The second study used a mixed ANOVA to assess differences in students’ attitudes, measuring at two time points and between schools. Furthermore, a one-way ANOVA was performed to determine whether there were variations depending on students’ physical activity level. Results. According to the findings of this study, personal variables eliminated the significance of social variables, with task orientation having the highest beta (.33). The results also revealed a significant interaction between measurements in Grades 7 and 8, as well as between schools. Moderately and highly active students had more positive attitudes than sedentary students in both cohorts. Conclusions. Task orientation and personal progress should be emphasized to increase students’ motivation. Nevertheless, a task-supportive climate could improve their intrinsic motivation for lifelong exercise.